Flavonoids as therapeutic agents for epilepsy: unveiling anti-inflammatory and antioxidant pathways for novel treatments - Zhang, Ya; Hu, Xizhuo; Zou, Li-Qun (Frontiers in Pharmacology, 2024)
Epilepsy, a chronic neurological disorder affecting millions globally, is often exacerbated by neuroinflammation and oxidative stress. Existing antiepileptic drugs primarily manage symptoms, leaving the disease's progression largely unaddressed. Flavonoids, ubiquitous plant metabolites with potent anti-inflammatory and antioxidant properties, show promise in epilepsy treatment. Unlike conventional therapies, they target multiple pathophysiological processes simultaneously, offering a comprehensive approach to this complex neurological disorder. This review explores the dual role of flavonoids in mitigating neuroinflammation and reducing oxidative stress through various molecular pathways. By inhibiting key inflammatory mediators and pathways such as NF-κB, MAPK, JNK, and JAK, flavonoids offer neuronal protection. They enhance the body's natural antioxidant defenses by modulating enzyme activities, including superoxide dismutase, catalase, and glutathione peroxidase. Moreover, flavonoids influence crucial antioxidant response pathways like PI3K/AKT, Nrf2, JNK, and PKA. Despite their therapeutic promise, the low bioavailability of flavonoids poses a considerable challenge. However, cutting-edge strategies, including nanotechnology and chemical modifications, are underway to improve their bioavailability and therapeutic efficacy. These advancements support the potential of flavonoids as a valuable addition to epilepsy treatment strategies.